2018
DOI: 10.3892/ol.2018.8904
|View full text |Cite
|
Sign up to set email alerts
|

A risk score staging system based on the expression of seven genes predicts the outcome of bladder cancer

Abstract: Bladder cancer (BLCA) is among the most malignant types of cancer. At present, the prognostic tools available for this disease are insufficient. In the present study, the transcriptome of 1,049 BLCA samples from four datasets from the Gene Expression Omnibus and The Cancer Genome Atlas (TCGA) were analyzed. By utilizing the RNA-seq data provided by TCGA, a risk score staging system model was built to predict the outcome of patients with BLCA using random forest variable hunting and Cox multivariate regression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Expression of PDGFRA was reported in BLCA specimens; however, such report lacked sufficient experimental study (Terada, 2009;Terada, 2013). AHNAK was identified as a unique intracellular protein with different expression level and subcellular localization between BLCA sample and control (Lee et al, 2018); whereas, its prognostic value was observed in other studies (Chu et al, 2018;Wu et al, 2019). High expression of EDNRA was found to be associated with poor outcome in patients with advanced BLCA in a bioinformatics report (Laurberg et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
“…Expression of PDGFRA was reported in BLCA specimens; however, such report lacked sufficient experimental study (Terada, 2009;Terada, 2013). AHNAK was identified as a unique intracellular protein with different expression level and subcellular localization between BLCA sample and control (Lee et al, 2018); whereas, its prognostic value was observed in other studies (Chu et al, 2018;Wu et al, 2019). High expression of EDNRA was found to be associated with poor outcome in patients with advanced BLCA in a bioinformatics report (Laurberg et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
“…Liu et al (2018)[39]50.83/ n = 119;0.68/ n = 1206ACADS; C1QTNF9B; RP11-60 L3.1; CTD-3195I5.3; has-miR-3913-1; has-miR-891aJ. Chu et al (2018)[40]30.615/ n = 407NA/ NA7ZNF230; BCL2L14; AHNAK; TMEM109; APOL2; AGER; AOC2Z. Xu et al (2019)[41]NA0.735/ n = 412NA/ NA11MXRA7; EMP1; TNFA1P8L3; SERPINB12; SAPCD1; GABRG1; PLEKHG4B; ABCA4; PTPRR; XAGE2; PEX5LNote: NA represents “not available”, Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple genes, processes and stages are involved in the development of bladder cancer [20]. Abnormalities in apoptosis and cell EMT changes have been closely correlated with bladder cancer progression [21].…”
Section: Discussionmentioning
confidence: 99%